Penggunaan Metode meCUE 2.0 dalam Mengukur Pengalaman Pengguna pada Aplikasi ”OYO” - Joosten Joosten; Fandi Halim; Albion Myron; Freddy Tumbur Halomoan Marpaung (Maranatha University Press, 2023)
This research was conducted to measure user experience on the OYO hotel booking application. User experience was measured by the meCUE 2.0 method which uses a Likert scale of 7. Then there are 10 instruments consisting of usefullness, usability, visual aesthetics, status, commitment, positive emotions, negative emotions, product loyalty, intention to use, and overall evaluation. The tool for processing survey data is the meCUE questionnaire which aims to see the possibility of a comprehensive end-user rapid assessment. Questionnaire links are distributed online and are needed in retrieving survey data. After collecting survey data, the measurement results obtained from 10 instruments were 5.20 (usefullness), 5.67 (usability), 5.33 (visual aesthetics), 4.27 (status), 2.90 (commitment), 4 .66 (positive emotions), 2.66 (negative emotions), 3.58 (product loyalty), 3.85 (intention to use) and 3.33 (overall evaluation). The results are considered quite good overall.